2018
DOI: 10.1371/journal.pone.0191335
|View full text |Cite
|
Sign up to set email alerts
|

Different transfer pathways of an organochlorine pesticide across marine tropical food webs assessed with stable isotope analysis

Abstract: Chlordecone is a persistent organochlorine pesticide used in the banana fields of the French West Indies from 1972 to 1993. Three marine habitats (mangroves, seagrass beds and coral reefs) of two study sites located downstream contaminated rivers were chosen to evaluate the level of contamination of marine food webs. On each habitat, the food chain collected included suspended organic matter, primary producers (macroalgae, algal turf, seagrass), zooplankton, symbiotic organisms (corals, sea anemones), primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 48 publications
2
12
0
1
Order By: Relevance
“…In the present study, the TMF value for total DDTs exceeded 1, indicating that the level of DDT bioamplify along with the food webs. In this study, the TMF values were 1.18 and 1.19 for p,p'DDE, and ΣDDT respectively which is in agreement with studies reported by Kidd et al (2001) in African lake food web (TMF for DDT = 1.16, TMF DDE = 1.25,), also constant with marine food web investigation by Dromard et al (2018), with TMF of chlordecone ranged from 1.07-1.25. However, the TMF values of ΣDDT in this study were lower than those reported by Sun et al (2017) in South China mangroves with TMF of 2.61 and 2.76 for DDT and PCB respectively.…”
Section: Relationships Between Stable Isotope and Concentration Of Posupporting
confidence: 91%
“…In the present study, the TMF value for total DDTs exceeded 1, indicating that the level of DDT bioamplify along with the food webs. In this study, the TMF values were 1.18 and 1.19 for p,p'DDE, and ΣDDT respectively which is in agreement with studies reported by Kidd et al (2001) in African lake food web (TMF for DDT = 1.16, TMF DDE = 1.25,), also constant with marine food web investigation by Dromard et al (2018), with TMF of chlordecone ranged from 1.07-1.25. However, the TMF values of ΣDDT in this study were lower than those reported by Sun et al (2017) in South China mangroves with TMF of 2.61 and 2.76 for DDT and PCB respectively.…”
Section: Relationships Between Stable Isotope and Concentration Of Posupporting
confidence: 91%
“…Bioaccumulation phenomena of chlordecone have been demonstrated experimentally (Bahner 1977) and in the field (Dromard et al 2018). Two processes of bioaccumulation were demonstrated in the present study.…”
Section: Discussionsupporting
confidence: 61%
“…Chlordecone adsorbed on microplastic particles suggests the possible existence of a new pathway of transfer of the molecule into marine trophic food-webs. However, while models of accumulation and biomagnification of chlordecone in the marine environment have been studied (Coat et al 2011, Dromard et al 2018, none of them have considered this potential pathway of contamination. The competitiveness of chlordecone compared to other pollutants, such as DDT or DDE found in the waters around Guadeloupe, is also not known.…”
Section: Discussionmentioning
confidence: 99%